2020
DOI: 10.3390/electronics9111982
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Performance and Assessment Study of a Current-Fed DC-DC Resonant Converter Combining Si, SiC, and GaN-Based Power Semiconductor Devices

Abstract: This paper focuses on the main reasons of low efficiency in a current-fed DC-DC resonant converter applied to photovoltaic (PV) isolated systems, comparing the effects derived by the overlapping time in the gate-signals (gate-source voltage) combining silicon (Si), silicon carbide (SiC), and gallium nitride (GaN)-based power devices. The results show that unidirectional switches (metal–oxide–semiconductor field-effect transistors (MOSFETs) plus diode) present hard switching as a result of the diode preventing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…At higher frequencies, such as 6.78 MHz, switching losses become dominant, significantly reducing the efficiency of the system and increasing power losses on the transistor. To this aim, gallium nitride (GaN) transistors were considered (model EPC2023) [31][32][33][34]. To drive the four GaN MOSFETs of the bridge, two independent square signals were used.…”
Section: Resultsmentioning
confidence: 99%
“…At higher frequencies, such as 6.78 MHz, switching losses become dominant, significantly reducing the efficiency of the system and increasing power losses on the transistor. To this aim, gallium nitride (GaN) transistors were considered (model EPC2023) [31][32][33][34]. To drive the four GaN MOSFETs of the bridge, two independent square signals were used.…”
Section: Resultsmentioning
confidence: 99%
“…𝑡 𝑜𝑛 = 𝑄 𝐼 𝐺𝑜𝑛 (12) 𝑡 𝑜𝑓𝑓 = 𝑄 𝐼 𝐺𝑜𝑓𝑓 (13) The switching losses referred to the diode are related to reverse recovery. Therefore, due to the use of SiC technology devices, which present zero reverse recovery charge, it will be disregarded in this paper.…”
Section: Losses Analysis For the Implemeted Boost Convertersmentioning
confidence: 99%
“…A study on system stability revealed that the overlap time affects the system stability, but it is not explained in detail [14]. A study compared losses due to overlap time in different power devices and analyzed the degree of loss reduction in different power device combinations [15]. A natural soft-commutation PWM scheme reduces the overlap duration by achieving natural soft commutation during the switching process, but it only considers the unity power factor [16].…”
Section: Introductionmentioning
confidence: 99%